Washington consensus and implications on economic and social inequity (2019)
The essential aim of this study is to discuss the most important features of the “Washington Consensus” or neoliberal policies, and its main repercussions in the social and economic spheres. This article presents a critical view of the neoliberal measures that have increased inequality, and have resulted in less effective mechanisms to achieve economic and political inclusion within the context of updated social conditions. The political support for conception, implementation and assessment of the “Washington Consensus” has being instituted in the wellbeing and better living conditions of the more powerful social groups. Relationships of neoliberalism and globalization are discussed here as well. Rescue of public sphere and competences and a more active role of inclusive institutions are part of the conclusions and final considerations of this study. © 2019, Universidad del Zulia. All rights reserved.